Analysis of MIMO antenna array based on electromagnetic vector sensor - Jie ZHOU; Lin QIU; Kikuchi HISAKAZU (Tongxin xuebao)
EVS(electromagnetic vetor sensor) signal processing method was combined with traditional MIMO signal processing method and three-dimensional channel model of multi-antenna array was set up.The algorithm of multiple signal classification (MUSIC) was adopted to make spatial spectrum estimation for direction of arrival (DOA) signal,analytical expressions of three-dimensional spatial channel was derived base on EVS for MIMO receiver system and the relationship between EVS signal processing and MIMO multipath channel correlation was clarified.To compare with tra-ditional MIMO antenna array,EVS array possesses abilities of obtaining multidimensional polarization information,processing spatial and polarization domain for arrival signal and degrading effects of spatial factors on MIMO channel capacity.Theoretical analysis and simulation results indicate that EVS array provide more advantages than traditional scalar sensor array on enhancing MIMO system performance.